ANALISIS STATISTICAL QUALITY CONTROL DALAM UPAYA MENGURANGI JUMLAH PRODUK CACAT DI PABRIK ROTI THE LI NO’U BAKERY - RAHMAWATY AHMAD; RESMAWAN RESMAWAN; DEWI RAHMAWATY ISA (Jambura Journal of Probability and Statistics, 2020)
Quality control is a technical and management activity which measures the quality characteristics of a product or service. Statistical quality control can be used to find production errors that result in defective products so that further corrective action can be taken to overcome them. The objective to be achieved in this research is to determine the Statistical Quality Control (SQC) method with pareto diagrams, control charts, cause and effect diagrams and 5W+1H analysis applied to The Li No'u Bakery in controlling quality to minimize failed products. The data in this study were obtained through direct observation and field interviews. Data analysis tools used are control charts, pareto diagrams, cause and effect diagrams and 5W + 1H analysis. Through a cause and effect diagram, the main factors causing the failure of bakery products at The Li No'u Bakery are manufacturers/employees. This is because the operator fails in making bakery products both the preparation of raw materials, the production process and packaging. So training is needed on making the dough, how to put bread and how to covenant and employee order according to the standard of The Li No'u Bakery.